The Effect Of Dispatch Resource Management (DRM) Training On Flight Operations Officer (FOO) Performance - Lubis, Marsel; Kurniawanto, Hari; Adrian, Dede; Demmy Setyo; Yohanes, Frits (FTK UNSURYA, 2025)
This study aims to analyze the impact of Dispatch Resource Management (DRM) on team decision-making, communication and coordination, as well as the operational efficiency of Flight Operations Officers (FOO). Using a quasi-experimental design of the pre-test post-test control group, it was then divided into an experimental and control group of 20 FOOs from Batik Air. Data was collected through structured observations, questionnaires, and performance simulations at Batik Air Cengkareng training facilities. Using paired t-tests and independent t-tests, the results were analyzed. The results showed a significant improvement in all FOO performance variables in the experimental group after DRM training (p < 0.001), while the control group showed no significant change. These findings conclusively demonstrate the effectiveness of DRM in improving the performance of multidimensional FOO and offer a novelty with empirical validation specific to DRM for FOO. This research has important implications for the aviation industry in adopting DRM training to improve safety and operational efficiency.